Environmental, social and governance, and tax avoidance: Study in ASEAN countries - Mukhtaruddin; Novriansa, Agil; Siahaan, Hani Maria Angel (Asian Economic and Financial Review, 2025)
This study investigates how business activities related to governance, social, and environmental performance affect tax avoidance practices in ASEAN countries. Using firm size, profitability, and leverage as control and moderating variables, a sample of 87 non-financial service businesses from five ASEAN nations Indonesia, Singapore, Malaysia, Thailand, and the Philippines that are listed on stock exchanges was used in the study. The sample was determined by the same criteria. E-Views was used for hypothesis testing. This study found that tax avoidance practices are influenced by governance, social, and environmental performance. Firm size, profitability, and leverage are used to control the stability and consistency of the impact of governance, social, and environmental performance on tax avoidance practices. The relationship between environmental, social, and governance performance and tax avoidance practices can be moderated by firm size and profitability; however, leverage cannot. Environmental, social, and governance performance are tools for businesses to avoid tax payments. These practices are influenced by firm size, profitability, and leverage, with moderation by firm size and profitability. The number of companies listed on stock exchanges in the five ASEAN countries is 3,634, but only a few companies disclose their environmental, social, and governance information. To ensure that businesses disclose sustainability concerns, assess their performance, and comply with tax regulations, governments and sustainability-related organizations must support and supervise the implementation of sustainability activities.